CHAGATAI STATE IN MEDIEVAL STATESMANSHIP AND STATE ADMINISTRATION - Abduazimov, D. B.; Khasanboev, T. F. (Mental Enlightenment Scientific-Methodological Journal, 2024)
This article focuses on explaining the role and importance of Chagatai state in the medieval statehood and state administration, its role and importance in the history of our statehood. It also briefly describes the preserved traditions of management in this period and the newly introduced tools and positions in management.